(3efgGL GdHjGf ajeG jSJYedg GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s ((3jGbhJ Hf YHO Gddg , YJjb GdMcje CHj GdaVGFd Hf YjSi GHf CHj GdaVGFd GdeJWHH s)
(3ChdgG (B:s
(3hcKjQGA ef cd hGMO CQHYI OQGge , Cajhf , OGfb hfUa jOb bOjVGa ai HYV GdfSN EbdjejkG s
(3BNQgG (B:s
(3jfKhf hgh GdKGaSjG , Ci UeZ GdSPGH GdLHdi , hgh MGQjGHS jSgd GdHdZe hbO ESJhai PcQg hTQMg ai HGH GdKGA s
(3fSNI KGefIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B260 s
Keywords: (3GdWHs